(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
This paper is an effort to explore some possibilities of FAP (Functional Analytic Psychotherapy) as a method of supervision. Four behavior therapists treating borderline patients took part in this study. The supervison sessions were individual and monthly. They were recorded, transcribed and submitted to a qualitative inductive analysis. From this analysis, two categories of relevant therapist behavior emerged. Both occurred in the interactions between therapist and supervisor, but were directly relevant for problems that the therapists experienced in relation their borderline clients: (1) Reason giving / experiential avoidance and (2) despair. It is concluded that close attention to interpersonal patterns that occur during supervision can produce in-vivo learning opportunities for supervisees. This makes FAP a viable approach to enhance supervision for therapists with borderline clients.